Prevalence and risk factors of COVID-19-related generalized anxiety disorder among the general public in China: a cross-sectional study - Yi Xia; Qi Wang; Lushaobo Shi; Zengping Shi; Jinghui Chang; Richard Xu; Huazhang Miao; Dong Wang (PeerJ, 2023)
Objective This study aimed to estimate the prevalence of generalized anxiety disorder in China during the coronavirus disease 2019 (COVID-19) pandemic and identify its associated factors. Methods A cross-sectional study was conducted among the general population in China from March 16 to April 2, 2020. The participants were recruited using stratified random sampling. Data on demographic characteristics and COVID-19 related factors were obtained using self-administered questionnaires. The anxiety score was measured based on the Chinese version of the Generalized Anxiety Disorder 7-item Scale (GAD-7). Results The study comprised 10,824 participants, of which 37.69% had symptoms of anxiety. The risk factors for anxiety symptoms included poor self-reported health (OR = 1.672, p < 0.001), chronic diseases (OR = 1.389, p < 0.001), and quarantine (OR = 1.365, p < 0.001), while participants’ perceptions that COVID-19 would be controlled was a protective factor (OR = 0.774, p < 0.001). The interactions between quarantine and self-reported health (p < 0.001), as well as between perceptions of COVID-19 and self-reported health (p < 0.001) were found to have a significant effect on GAD-7 scores. Conclusions Self-reported health status, chronic diseases, quarantine, and perceptions of COVID-19 were significantly associated with GAD-7 scores, indicating that mental health interventions are urgently needed during pandemics, especially for high-risk groups.